Ethnic enclaves and immigrant economic integration - Simone Schüller; Tanika Chakraborty (IZA World of Labor, 2022)
Immigrants tend to live in clusters within host countries. Does clustering in ethnic enclaves explain the persistent differences in skill, employment rates, and earnings between immigrants and the native population? Empirical studies consistently find that residing in an enclave can increase earnings. While it is ambiguous whether employment probabilities are also affected or whether earnings benefits accrue to all immigrants, irrespective of their skill levels, it is clear that effects are driven by enclave "quality" (in terms of income, education, and employment) rather than enclave size.
Keywords: J15; R23; Z10; 330; immigrant concentration; ethnic networks; immigrant labor market integration